Customer service of a fast-food chain in the city of Patos - PB: the impact of innovation on the quality of service provided (Research, Society and Development, 2023)
The present article aims to study the impact of innovation on the quality of customer service in a fast-food chain in the city of Patos-PB, as well as to point out, through the collection of information, the points that consumers see as a lack of service and score opportunities for improvement for the analyzed chain. Within this context, the methodology adopted was based on carrying out a qualitative and quantitative case study, collecting data through questionnaires and analyzing them, to understand the degree of consumer satisfaction and their perception of the service provided. After collecting the data, it could be seen that, despite the satisfaction of most customers, improvements and investments in innovation are still needed to reach even higher levels in the quality of services provided by the chain, always aiming at optimal satisfaction.